VITREORETINAL COMPLICATIONS AFTER PENETRATING KERATOPLASTY. Issue 11 (November 2016) - Park, Yuli; Kim, Min Hee; Won, Jae Yon; Kim, Hyun Seung; Park, Young-Hoon
Abstract : Purpose: To evaluate the time, incidence, and visual outcome of vitreoretinal complications after penetrating keratoplasty (PK). Methods: A retrospective chart review of 1, 594 eyes that underwent PK was conducted. Preoperative characteristics, visual significance, and postoperative vitreoretinal complications were analyzed. Results: The incidence of vitreoretinal complications after PK was 3.3% (52/1, 594). The mean follow-up period was 38.5 ± 29.8 months. The mean time for vitreoretinal complications to occur was 4.8 months. The most common vitreoretinal complication was vitreous hemorrhage (0.75%), and others included choroidal detachment (0.7%), endophthalmitis (0.6%), and retinal detachment (0.5%). Majority of vitreous hemorrhage, endophthalmitis, and choroidal detachment occurred within 1 month postoperatively, but most cases of cystoid macular edema and epiretinal membrane occurred after 3 months. At follow-up after PK, the mean corrected distance visual acuity was worse among eyes that experienced vitreoretinal complications compared with eyes that did not ( P = 0.013). Conclusion: Vitreoretinal complications after PK occurred in a significant percentage, resulting in persistent reduction of corrected distance visual acuity. Given this, it is of particular importance to control intraoperative and postoperative intraocular pressure, infection, and inflammation which will contribute to decrease in the incidence of vitreoretinal complications after PK. Abstract : Vitreoretinal complications after penetrating keratoplasty occurred in a significant percentage, resulting in persistent reduction of visual acuity. Given this, it is of particular importance to control intraoperative and postoperative intraocular pressure, infection, and inflammation which will contribute to decrease in the incidence of vitreoretinal complications after penetrating keratoplasty.